PENERAPAN STRATEGI REACT (RELATING, EXPERIENCING, APPLYING, COOPERATING, TRANSFERRING) UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SMP - Abdul Rosyid; Evan Farhan Wahyu Puadi (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2016)
This study aims to examine in depth the improvement of mathematical problem solving abilities of students who take part in learning through the REACT strategy. The research method chosen was quasi-experimental research with a non-equivalent control group design. In this experimental design there were two groups of samples, the pretest, the different treatments, and the presence of posttest. The data obtained during the study were analyzed using SPSS 19 software to obtain a conclusion. After analyzing the data, it was concluded that an increase in students 'mathematical problem solving abilities whose learning through the REACT strategy was better than the improvement of students' mathematical problem solving abilities in conventional learning